Effects of horizontal gene transfer on bacteriophage infectivity - Nabila, Noshin; Mithil, Farzana Akter; Hassan, Huma (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.